Multiplexed measurement of protein diffusion in Caenorhabditis elegans embryos with SPIM-FCS. (24th December 2015) - Struntz, Philipp; Weiss, Matthias
Abstract: Quantifying the diffusion behavior of proteins in different environments, e.g. on cellular membranes, is a key step in uncovering the vital action of protein networks in living organisms. While several established techniques for local diffusion measurements exist, the life sciences are currently in need of a multiplexed, i.e. spatially parallelized, data acquisition that allows for obtaining diffusion maps with high spatiotemporal resolution. Following this demand, the combination of camera-based single-plane illumination microscopy (SPIM) and fluorescence correlation spectroscopy (FCS) has recently emerged as a promising approach. So far, SPIM-FCS has mainly been used to assess the diffusion of soluble particles and proteins in vitro and in culture cells, but due to a particularly low photobleaching and -toxicity the method is also well applicable to developmental organisms. Here, we have probed the performance of SPIM-FCS on an established developmental model organism, the small nematode Caenorhabditis elegans . In particular, we have quantified the diffusion of the peripheral membrane protein PLC1 in the embryo's cytoplasm and on the plasma membrane. As a result, we were able to derive diffusion maps of PLC1 in both compartments in multiple individuals, showing the spatially varying diffusion coefficients across the embryo. Our data also report on the dissociation kinetics of PLC1 from the plasma membrane, hence underlining that SPIM-FCS can be used to explore key features of peripheral membrane proteins in fragile developmental model organisms.